Influence of fatty acid‐free diet on mammary tumor development and growth rate in HER‐2/neu transgenic mice12. Issue 1 (4th October 2012) - Rossini, Anna; Zanobbio, Laura; Sfondrini, Lucia; Cavalleri, Adalberto; Secreto, Giorgio; Morelli, Daniele; Palazzo, Marco; Sommariva, Michele; Tagliabue, Elda; Rumio, Cristiano; Balsari, Andrea
Abstract Numerous investigations have found a relationship between higher risk of cancer and increased intake of fats, while results of clinical studies of fat reduction and breast cancer recurrence have been mixed. A diet completely free of fats cannot be easily administered to humans, but experimental studies in mice can be done to determine whether this extreme condition influences tumor development. Here, we examined the effects of a FA‐free diet on mammary tumor development and growth rate in female FVB‐neu proto‐oncogene transgenic mice that develop spontaneous multifocal mammary tumors after a long latency period. Mice were fed a fatty acid‐free diet beginning at 112, 35, and 30 days of age. In all these experiments, tumor appearance was delayed, tumor incidence was reduced and the mean number of palpable mammary tumors per mouse was lower, as compared to standard diet‐fed mice. By contrast, tumor growth rate was unaffected in mice fed the fatty acid‐free diet. Plasma of mice fed the fatty acid‐free diet revealed significantly higher contents of oleic, palmitoleic and 20:3ω9 acids and lower contents of linoleic and palmitic acids. In conclusion, these findings indicate that a FA‐free diet reduces tumor incidence and latency but not tumor growth rate, suggesting that a reduction in dietary FAs in humans may have a protective effect on tumorigenesis but not on tumors once they appear. J. Cell. Physiol. 228: 242–249, 2013. © 2012 Wiley Periodicals, Inc.